2014
DOI: 10.4081/jphr.2014.157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Epidemiology of Human Papillomavirus Infection in Italian Women with Cervical Cytological Abnormalities

Abstract: BackgroundHuman papillomavirus (HPV) infection is the most common sexually transmitted infection and high-risk HPV types are a necessary cause for the development of cervical cancer. The present study investigated the HPV-type specific prevalence in 650 women, aged 15-76 years, with cytological abnormalities and the association between HPV infection and cervical disease in a subset of 160 women for whom cytological results for Pap-Test were available, during the period 2008-2011 in Cagliari (Southern Italy).De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
18
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
10
18
2
Order By: Relevance
“…HPV16 together with HPV18 are known to be responsible for approximately 70% of the cervical cancer cases worldwide [6, 8, 9]. The prevalence of HPV18 has been reported in other studies, ranging between 1.8% and 16.3% [20, 21, 23, 27]. In agreement with the aforementioned studies, the prevalence of HPV18 in the present study was 4.1%.…”
Section: Discussionsupporting
confidence: 91%
“…HPV16 together with HPV18 are known to be responsible for approximately 70% of the cervical cancer cases worldwide [6, 8, 9]. The prevalence of HPV18 has been reported in other studies, ranging between 1.8% and 16.3% [20, 21, 23, 27]. In agreement with the aforementioned studies, the prevalence of HPV18 in the present study was 4.1%.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, participants with ≄1 HR-HPV type were more often diagnosed with HSIL than participants with LR-HPV. Similar observations concerning the association of poor cytological diagnosis with carcinogenic HPV types have been previously reported (36,38). In all grades of cytological diagnosis, HPV16 was the most common HPV type (ASC-US, 29.46%; LSIL, 29.58%; HSIL, 43.22%).…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, an outdated HPV classification system with several probably HR-HPV types identified that the HR-HPV prevalence was 81.50% in participants <30 years of age. This is slightly lower than the prevalence previously described for other regions in Germany (88.40%) (36). However, using a classification system based on novel biological evidence, which revealed that more HPV types exhibit carcinogenicity than previously acknowledged (10,33), the prevalence of HR-HPV types identified by the present study increased to 91.53%.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Virtually all cases of cervical and anogenital cancer are caused by approximately 15 hrHPV genotypes [Muñoz et al, ]. HPV 16 is the most common type and is associated with about the 50% of all cases of cervical cancer [Lowy et al, ; Meloni et al, ].…”
Section: Introductionmentioning
confidence: 99%